Studies in Adsorption of Some Toxic Metal Ions on Citrus sinensis Skin and Coffea arabica Husk: Agricultural Byproduct - Jumle, Ravi; Narwade, M.L.; Usha Wasnik, Ms. (Asian Journal of Chemistry, 2010)
Adsorption of toxic metal ions like Hg2+, Pb2+ and transition metal Zn2+ ion on different agricultural byproducts were measured by UV-visible spectrophotometer-108. Adsorption of metal ions follows the order polymerized Citrus sinensis (mosambi) skin> Coffea arabica (coffee) husk for Hg2+ and Pb2+ and Citrus sinensis skin < Coffea arabica husk for Zn2+ metal ion. Citrus sinensis skin showed maximum adsorbing capacity for Hg2+ and Pb2+ metal ions. It could also be seen that Hg2+ metal ion is a good adsorbing adsorbate as compared to Pb2+ and Zn2+ metal ions. The values of Freundlich constants (n and k) are estimated from graph which are found to be 1/n < 1 and k > I.